Invertebrate trace fossils from the Pennsylvanian Rhode Island Formation of Massachusetts, USA - Getty, Patrick; Sproule, Robert; Stimson, Matthew; Lyons, Paul (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2017)
ABSTRACT A large open-pit quarry in Plainville, Massachusetts, has yielded fourteen invertebrate ichnotaxa from the Pennsylvanian Rhode Island Formation of the Narragansett Basin. These traces include Cochlichnus anguineus, Diplichnites cuithensis, Diplichnites gouldi, Diplopodichnus biformis, Gordia carickensis, Helminthoidichites tenuis, Lockeia isp., Mitchellichnus cf. ferrydenensis, Planolites montanus, Siskemia elegans, Stiallia pilosa, Stiaria intermedia, Tonganoxichnus buildexensis and Narragansettichnus fortunatus new ichnogenus and ichnospecies. Specimens were collected from talus and the depositional environment has been inferred from sedimentary structures. The sedimentology of the slabs on which the traces were preserved indicates that the rocks represent lake-margin and shallow lacustrine sedimentary facies. Distinct ichnofacies occur in the different sedimentary environments. The lake-margin traces belong to the Scoyenia ichnofacies and include traces of apterygote insects, arthropleurid myriapods, bivalved arthropods and vermiform animals in association with tracks of temnospondyl amphibians and diapsid reptiles. The lacustrine traces include arthropod trackways, fish trails and a newly named body imprint possibly produced by an aquatic mayfly larva. These shallow lacustrine traces are attributed to the Mermia ichnofacies.